Effect of Temperature and Current Density on Hydrogen Production for Polybenzimidazole Zirconium Phosphate Hybrid Membrane in Copper Chloride Electrolysis - Ahmad Kamaroddin , Mohd Fadhzir; Hj. Sabli, Nordin; Tuan Abdullah, Tuan Amran; Abdullah, Luqman Chuah; Siajam, Shamsul Izhar; Ripin, Adnan; Ahmad, Arshad (International Journal of Integrated Engineering, 2019)
Today, about 95 % of hydrogen gas supply is produced from steam methane reforming process, which uses substance from fossil fuel origin. This unsustainable source of hydrogen production also leads to greenhouse gases emission. Hence, this paper presents the promising future of exploiting an alternative to water electrolysis; the elevated temperature copper chloride electrolysis as a sustainable hydrogen production using polybenzimidazole based membrane. Temperature and current density are investigated in the range of 100 to 115 áµ’C and 0.1 to 0.5 A cm-2, respectively. Hybrid membrane PBI was synthesized with zirconium oxide (ZrO2) followed by phosphoric acid (PA) doping while pristine PBI and Nafion 117 used as a reference. The membrane properties are characterized using Metrohm Autolab PGSTAT302N, thermogravimetric analyzer, UV-Vis spectrometer, and Lloyd universal tensile tester. From the result, the hybrid PBI/ZrP membrane properties improved significantly compared to pristine PBI. The PBI/ZrP exhibited superior proton conductivity, thermally stable with high tensile strength. The efficiency of the electrolyzer for hydrogen production was ranging from 91 to 97 %. The mixing of the pristine PBI with ZrO2 and PA doping has produced hybrid PBI/ZrP membrane that can be a promising effective polymer electrolyte and budget-friendly compared to Nafion.